Analysis of Stochastic Diffusive Predator PreyModel with Hyperbolic Mortality Rate - Suvinthra, M.; Balachandran, K.; Sambath, M. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, we establish a Freidlin-Wentzell type large deviation principle for a diffusive predator-prey modelwith hyperbolic mortality rate perturbed by multiplicative type Gaussian noise. We implement the variational representation developed by Budhiraja and Dupuis to establish the large deviation principle for the solution processes.